The Influence of Leri Water Supplementation on the Growth and Production of White Oyster Mushrooms (Pleurotus Ostreatus) - Leopoldino Vasco Martins (MultiTech Publisher, 2023)
This study aimed to investigate the influence of leri water supplementation on mycelium growth, primordial appearance, fruiting body count, fruit body diameter, and wet weight, as well as the production of white oyster mushrooms (Pleurotus ostreatus). The research employed a Completely Randomized Design (CRD) with four treatments: A0 (control without leri water), A1 (20 ml of leri water), A2 (40 ml of leri water), and A3 (60 ml of leri water), with a 95% confidence level F-test. The results revealed that leri water supplementation significantly affected all observed variables. The treatment with 40 ml of leri water (A2) produced the highest mycelium growth with an average weight of 10.45 kg, the earliest primordial appearance, the highest fruiting body count (15.67), and the highest wet weight (372 kg). Meanwhile, the treatment with 60 ml of leri water (A3) resulted in the largest fruit body diameter (17 cm). Among the treatments, A2 with a 40% leri water nutrient supplement in the growing medium outperformed others, as it provided the necessary nutrients for mycelium growth and overall mushroom development.